2013
DOI: 10.1088/0004-637x/766/2/80
|View full text |Cite
|
Sign up to set email alerts
|

H2(v= 0,1) + C+(2P) → H+CH+STATE-TO-STATE RATE CONSTANTS FOR CHEMICAL PUMPING MODELS IN ASTROPHYSICAL MEDIA

Abstract: State-to-state rate constants for the title reaction are calculated using the electronic ground state potential energy surface and an accurate quantum wave-packet method. The calculations are performed for H 2 in different rovibrational states, v = 0, 1 and J = 0 and 1. The simulated reaction cross section for v = 0 shows a rather good agreement with the experimental results of Gerlich et al., both with a threshold of 0.36 eV and within the experimental error of 20%. The total reaction rate coefficients simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
104
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(116 citation statements)
references
References 68 publications
11
104
1
Order By: Relevance
“…The situation in the system under study is clearly immediate, favoring the formation of H 2 in v = 1 and 2. This provides another possibility for the formation of vibrationally excited H 2 , which is of interest in the chemistry of the interstellar medium because it allows the occurrence of endothermic reactions (Agundez et al 2010;Godard & Cernicharo 2013), as recently shown for the C + + H 2 system (Zanchet et al 2013). The initial rotational states of LiH (v = 0) considered are just j = 0 and 1, and its contribution to the total angular momentum can be neglected, such that J can be considered proportional to the classical impact parameter.…”
mentioning
confidence: 81%
“…The situation in the system under study is clearly immediate, favoring the formation of H 2 in v = 1 and 2. This provides another possibility for the formation of vibrationally excited H 2 , which is of interest in the chemistry of the interstellar medium because it allows the occurrence of endothermic reactions (Agundez et al 2010;Godard & Cernicharo 2013), as recently shown for the C + + H 2 system (Zanchet et al 2013). The initial rotational states of LiH (v = 0) considered are just j = 0 and 1, and its contribution to the total angular momentum can be neglected, such that J can be considered proportional to the classical impact parameter.…”
mentioning
confidence: 81%
“…Laboratory experiments (Hierl, Morris & Viggiano 1997) and quantum calculations (e.g. Zanchet et al 2013b), however, show that the reaction becomes exothermic when H * 2 , and not H 2 (v=0), is the reactant. The reaction rate k * then reaches the Langevin limiting case, and becomes almost independent of the temperature.…”
Section: The Role Of Vibrationally Excited H 2 In the Chemistrymentioning
confidence: 99%
“…Fig.10 of Hierl et al (1997) suggest a possible weak temperature dependence. Zanchet et al (2013b) performed quantum calculations to derive state-to-state reaction rates for the system C + and H 2 . In the following, we neglect the formation excitation of CH + and use the parametrized rate from Zanchet et al (2013a) for H 2 (v = 1) ( Table 3) The theoretical calculations are a factor 4 lower than the laboratory work from Hierl et al (1997) (Fig.…”
Section: Appendix A: Chemical Reaction Ratesmentioning
confidence: 99%